2019
DOI: 10.1213/xaa.0000000000000855
|View full text |Cite
|
Sign up to set email alerts
|

Rare Case of Transcutaneous Oxygen Desaturation in a Cancer Patient: A Case Report and Diagnostic Approach for a Recurrent Problem

Abstract: We present a case of a 73-year-old cancer patient with low transcutaneous oxygen saturation who was transferred to the intensive care unit after deployment of the rapid response team. Differential diagnosis remained broad until methemoglobinemia (MetHb) was detected. MetHb was induced by administration of rasburicase, which was given to prevent tumor lysis syndrome. In a follow-up examination, glucose-6-phosphate dehydrogenase deficiency was found to be the cause of MetHb after rasburicase exposure. Diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Among the included studies, 21 studies reported 1 patient each, and 3 studies reported 2 patients each who developed methemoglobinemia followed by rasburicase administration. The majority of patients were previously diagnosed with lymphoma, T-cell or acute lymphoblastic leukaemia, Non-Hodgkin lymphoma, chronic lymphocytic leukaemia, Burkitt's lymphoma, and few were diagnosed with gout, Neuroendocrine tumour, Status epileptics, IgA variant or refractory aggressive multiple myeloma, sporadic adenomatous polyposis syndrome and metastatic colon cancer, pulmonary sarcoidosis and mycosis fungoides and AIDS 5,1032 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the included studies, 21 studies reported 1 patient each, and 3 studies reported 2 patients each who developed methemoglobinemia followed by rasburicase administration. The majority of patients were previously diagnosed with lymphoma, T-cell or acute lymphoblastic leukaemia, Non-Hodgkin lymphoma, chronic lymphocytic leukaemia, Burkitt's lymphoma, and few were diagnosed with gout, Neuroendocrine tumour, Status epileptics, IgA variant or refractory aggressive multiple myeloma, sporadic adenomatous polyposis syndrome and metastatic colon cancer, pulmonary sarcoidosis and mycosis fungoides and AIDS 5,1032 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Heinz bodies were demonstrated on supravital staining with methylene blue. 15 out of 27 patients were presented with some degree of haemolytic anaemia 5,1030 (Table 4).…”
Section: Resultsmentioning
confidence: 99%